MALIN KUNDANG PULANG KAMPUNG, KARYA AHMAD MUCHLISH: MENDEKONSTRUKSI LEGENDA MALIN KUNDANG - Syam, Essy (Jurnal Ilmu Budaya, 2014)
To deconstruct is to undermine a universal idea or a stable meaning. It is led by a perception in which the deconstructionists believe that theres no stable meaning because every meaning can be undermined. Related to that, this writing is analyzing a short story entitles Malin Kundang Pulang Kampung which deconstructs the legendary story Malin Kundang from West Sumatra.